El cine y su narrativa: recurso para la enseñanza de la Historia y la formación del profesorado - Guerrero Elecalde, Rafael (2020)
This article contains an educational implantation oriented to reflection on the use of cinema as a didactic resource for the training of future History teachers. For this, a theoretical-practical workshop was developed with films which contents and themes were closely related to the program of the subject Modern History that is taught at the Faculty of Philosophy and Humanities of the National University of Córdoba (Argentina). The attendees of this course deepened in the acquisition of competence through pedagogical-didactic tools applied to the use of cinema for the transmission of modern history content. Also, they considered the virtues of the use of films in the classroom, their didactic value and their usefulness for teaching History. The analysis of the opinions collected helped us reach various conclusions that may serve to improve teaching activity in the following courses.